India's turn : understanding the economic transformation - Subramanian, Arvind (New Delhi : Oxford University Press, 2008)
On economic policies pursued in Indian economy post 1991 watershed year; articles co-authored with many other writers.
Includes bibliographical references and index.
Keywords: India -- Economic policy -- 1991-